Differential use of trophic resources between an exotic and a coexisting native snail - Altieri, Paula; Paz, Laura Estefanía; Ferreira, Ana Clara; Colpo, Karine Delevati; Rodrigues Capítulo, Alberto; Jensen, Roberto; Costa, Vladimir [UNESP]; Ocon, Carolina (Springer Nature, 2022)
Knowing the interactions between exotic and native species is essential to establish possible threats to the local fauna. In this study, we assessed the use of food resources and diet overlap between a recently introduced snail, Sinotaia quadrata, and a native species, Pomacea canaliculata. We analyzed the gut content and stable isotope of snails and resources in a lowland stream where both species coexist. Both Schoener’s and isotope dietary overlap indexes supported dietary overlap. Conversely, gut content analysis showed differences in consumption: S. quadrata consumed more detritus and diatoms than P. canaliculata, whose diet was characterized by detritus and macrophyte remains. Macrophytes were the resource that most contributed to the diet of both species, as shown by stable isotope mixing models. The combination of both techniques, gut content and stable isotope analysis, indicated that S. quadrata consumed macrophyte detritus while P. canaliculata ate fresh macrophytes. This difference indicates differential use of food resources between the studied species coexisting in a lowland stream. Although no negative trophic interaction was found, we highlight the importance of continuing to monitor interactions for other resources and studying possible risks to the local fauna.
Keywords: Gut contents; Non-native species; Pomacea canaliculata; Sinotaia quadrata; Stable isotopes